Frequency and Determinants of Poststroke Cognitive Impairment at Three and Twelve Months in Chile - Delgado, Carolina; Donoso, Archibaldo; Orellana, Patricia; Vásquez, Carolina; Díaz, Violeta; Behrens, María Isabel (Dementia and geriatric cognitive disorders, 2010)
Background: A higher risk of poststroke cognitive impairment (CI) has been reported in Hispanics in a US cohort but has not been systematically studied in Latin America. Objectives: Our purpose was to investigate the frequencies and determinants of poststroke CI in the hispano-mestizo population of Santiago, Chile. Methods: A prospective study of hospitalized patients aged >60 years admitted with an ischemic or hemorrhagic stroke was conducted. The cognitive status was determined at 3 and 12 months after the stroke by informant questionnaires, neuropsychological testing and clinical diagnosis. Cardiovascular risk factors, brain imaging and stroke features were analyzed using regression models to establish determinants for poststroke CI. Results: A total of 164 patients (mean age = 72 ± 7.5 years) were recruited. Out of 122 patients (74%) evaluated at 3 months, 81 (66%) had CI. Out of 101 patients (62%) evaluated at 12 months, 39 (39%) had CI no dementia, and 22 (22%) were demented. The new-onset dementia frequency at 1 year was 16%. Independent determinants for dementia were higher functional impairment at hospital egress (OR = 4.0), left-hemisphere large-vessel infarction (OR = 6.9) and a larger amount of white matter changes (OR = 1.3). Conclusions: In this first study on poststroke CI in Latin America, the frequencies and determinants of poststroke CI were similar to those in other cohorts of different ethnic origin.